Submergence tolerant rice: SUB1's journey from landrace to modern cultivar - Bailey-Serres, Julia; Fukao, Takeshi; Ronald, Pamela; Ismail, Abdelbagi; Heuer, Sigrid; Mackill, David (Springer, 2010)
Rice landraces tolerant of up to 2 weeks of complete submergence were collected from farmers’ fields in the 1950s. Success in fine mapping of SUBMERGENCE 1 (SUB1), a robust quantitative trait locus from the submergence tolerant FR13A landrace, has enabled marker-assisted breeding of high-yielding rice capable of enduring transient complete submergence. At the molecular level, SUB1 is a variable polygenic locus encoding two or three ethylene responsive factor (ERF) DNA binding proteins. All Oryza sativa accessions encode SUB1B and SUB1C at this locus. An additional ERF, SUB1A, is present at SUB1 in FR13A and other tolerant accessions. The induction of SUB1A expression by ethylene during submergence disrupts the elongation escape strategy typical of lowland and deepwater rice, by limiting ethylene-induced gibberellic acid-promoted elongation. Microarray and metabolite studies confirm that SUB1A orchestrates its effects on metabolism and growth in a submergence-dependent manner. Due to the conditional activity of SUB1A, new “Sub1” mega-varieties effectively provide submergence tolerance without apparent ill effect on development, productivity, or grain quality.